Effect of Asymptomatic Hyperuricemia on Mortality of Elderly Patients After Elective Percutaneous Coronary Intervention - Chen, Chen; Dong, Jianzeng; Lv, Qiang; Liu, Xinmin; Zhang, Qian; Du, Xin (Frontiers in Cardiovascular Medicine, 2022)
Purpose: The purpose of this study is to investigate the effect of asymptomatic hyperuricemia on mortality of elderly patients with coronary artery disease (CAD) after elective percutaneous coronary intervention (PCI). Methods: 1296 patients with coronary heart disease≥65 years old who had increased uric acid records and without gout history underwent elective PCI from January 2015 to January 2016 were enrolled. The hyperuricemia is defined as serum uric acid level > 420 μ mol/l (7 mg/dl) for males and > 357 μ mol/l (6 mg/dl) for females. Patients were divided into hyperuricemia group and non-hyperuricemia group. After an average of 519 days follow-up, the differences in postoperative mortality between the two groups were compared. Results There were 236 patients in hyperuricemia group and 1060 patients in non-hyperuricemia group. In hyperuricemia group, BMI was higher (P = 0.036); the proportions of patients with hypertension (P < 0.001) and myocardial infarction history (P = 0.046) were higher; white blood cells (P = 0.015) and triglyceride levels were higher (P < 0.001); and estimated glomerular filtration rate (P < 0.001) and high-density lipoprotein cholesterol level were lower (P =0.007). In addition, in hyperuricemia group, during hospitalization, the ratios of patients treated with diuretics (P < 0.001) and the number of PCI lesions were higher (P =0.030), and the complete revascularization rate was lower (P=0.017). The postoperative mortality rate (2.2% vs 7.6%, P < 0.001) of hyperuricemia group was significantly higher than that of non-hyperuricemia group. Multivariate Cox regression analysis showed that after adjusting for other factors, hyperuricemia was an independent risk factor for increased mortality after PCI (HR 2.786, 95% CI 1.233-6.297, P =0.014). Conclusion: Asymptomatic hyperuricemia is an independent risk factor for increased mortality of elderly patients with coronary heart disease undergoing elective PCI.